Effect of a carbohydrate-rich beverage on rate of cesarean delivery in primigravidae with epidural labor analgesia: a multicenter randomized trial - Ting Ding; Chun-Mei Deng; Xiao-Feng Shen; Yao-Wu Bai; Xiao-Lan Zhang; Ji-Ping Liu; Li-Juan Yang; Hai-Tao Yu; Lei Xie; Hong Chen; Dong-Liang Mu; Yuan Qu; et al. (BMC, 2022)
Abstract Background Labor represents a period of significant physical activity. Inefficient energy supply may delay labor process and even lead to cesarean delivery. Herein we investigated whether ingestion of a carbohydrate-rich beverage could reduce cesarean delivery in laboring women with epidural analgesia. Methods This multicenter randomized trial was conducted in obstetrician-led maternity units of nine tertiary hospitals in China. Primigravidae with single term cephalic pregnancy who were preparing for vaginal birth under epidural analgesia were randomized to intake a carbohydrate-rich beverage or commercially available low-carbohydrate beverages during labor. The primary outcome was the rate of cesarean delivery. Secondary outcomes included maternal feeling of hunger, assessed with an 11-point scale where 0 indicated no hunger and 10 the most severe hunger, and maternal and neonatal blood glucose after childbirth. Results Between 17 January 2018 and 20 July 2018, 2008 women were enrolled and randomized, 1953 were included in the intention-to-treat analysis. The rate of cesarean delivery did not differ between the two groups (11.3% [111/982] with carbohydrate-rich beverage vs. 10.9% [106/971] with low-carbohydrate beverages; relative risk 1.04, 95% CI 0.81 to 1.33; p = 0.79). Women in the carbohydrate-rich beverage group had lower subjective hunger score (median 3 [interquartile range 2 to 5] vs. 4 [2 to 6]; median difference − 1; 95% CI − 1 to 0; p < 0.01); their neonates had less hypoglycemia (1.0% [10/968] vs. 2.3% [22/956]; relative risk 0.45; 95% CI 0.21 to 0.94; p = 0.03) when compared with those in the low-carbohydrate beverage group. They also had higher rates of maternal hyperglycemia (6.9% [67/965] vs. 1.9% [18/953]; p < 0.01) and neonatal hyperglycemia (9.2% [89/968] vs. 5.8% [55/956]; p < 0.01), but none required special treatment. Conclusions For laboring primigravidae with epidural analgesia, ingestion of a carbohydrate-rich beverage compared with low-carbohydrate beverages did not reduce cesarean delivery, but relieved maternal hunger and reduced neonatal hypoglycemia at the expense of increased hyperglycemia of both mothers and neonates. Optimal rate of carbohydrate supplementation remains to be determined. Trial registration www.chictr.org.cn ; identifier: ChiCTR-IOR-17011994 ; registered on 14 July 2017.